Functional Component Production Capabilities in Milk Fermentation of Some Featured Lactic Acid Bacteria Species for Use in Different Food Processes - Tuğba Kök Taş; Fatma Ecemnur Duran; Nilgün Özdemir; Ebru Çubuk Demiralay (Fermentation)
This study examines the fermentation performance of featured bacteria (Lactobacillus acidophilus-ATCC-4356, Lactobacillus helveticus-ATCC-15009, Lactobacillus delbrueckii subsp. bulgaricus-ATCC-11842, Lacticaseibacillus casei-ATCC-393, Streptococcus thermophilus-ATCC-19258 (ST), and Bifidobacterium bifidum-ATCC-29521 (BB)) used in fermented dairy products and their impact on product quality. The main focus is on evaluating the metabolic activities, organic acid production, viscosity values, and sensory properties of probiotic strains such as L. acidophilus, L. bulgaricus, L. casei, L. helveticus, B. bifidum, and S. thermophilus. The strains were activated in a sterile milk medium and incubated until they reached a pH of 4.6. Then, pH, microbial enumeration, organic acid, sugar composition, vitamins A, D, E, K1, and K2 (menaquinone-7), and viscosity values were measured in the bacteria. Organic acid, sugar composition, and vitamins A, D, E, K1, and K2 (menaquinone-7) were analyzed with the HPLC method. Additionally, sensory analyses were performed, and volatile compounds were examined. L. casei demonstrated superiority in lactic acid production, while L. helveticus showed high lactose consumption. L. bulgaricus stood out in galactose metabolism. The highest viscosity was observed in products produced by B. bifidum. Differences in viscosity were attributed to exopolysaccharide (EPS) production and acid production capacity. A total of 62 volatile compounds were identified, with the highest levels of aromatic components found in products containing B. bifidum. The most preferred product, based on panel evaluations, was the fermented dairy product produced with L. acidophilus. As for aroma profiles, it was determined that the phenethyl alcohol, 3-methyl-1 butanol, and ethanol compounds are associated with B. bifidum, the hexanoic acid and 2-methylbutanal compounds are associated with the L. acidophilus, the hexanoic acid, 2-methylbutanal, 2-furanmethanol, and acetaldehyde compounds are associated with the L. bulgaricus, and the hexanoic acid, 2-methylbutanal, 2-heptanone, acetoin, and d-limonene are associated with the L. casei. On the other hand, the L. helveticus strain is associated with the hexanoic acid, 2-methylbutanal, and 2-heptanone, and the S. termophilus strain is associated with the hexanoic acid, hexanol, acetoin, 2,3-pentanedione, 1-butanol, and 3-methyl-2-butanone volatile aroma compounds. The determination of fat-soluble vitamins is particularly important for vitamin K1 and vitamin K2. In this study, the bacterial sources of these vitamins were compared for the first time. The menaquinone-7 production by L. helveticus was determined to be the highest at 0.048 µg/mL. The unique metabolic capacities of these prominent cultures have been revealed to play an important role in determining the aroma, organic acid content, viscosity, and overall quality of the products as a whole. Therefore, the findings of this study will provide the right strain selection for a fermented dairy product or a different non-dairy-based fermented product according to the desired functional properties. It also provides a preliminary guide for inoculation in the right ratios as an adjunct culture or co-culture for a desired property.